A second type of highly asphaltic crude oil seepage stranded on the South Australian coastline. (February 2020) - Corrick, Alexander J.; Hall, Philip A.; Gong, Se; McKirdy, David M.; Selby, David; Trefry, Christine; Ross, Andrew S.
Abstract: Strandings of semi-solid to solid asphaltic bitumen along the coastline of South Australia have been reported as far back as the late 1800s. Hitherto only a single variety, now referred to as asphaltite, has been attributed to seepage from the nearby Bight Basin. The geochemistry of the asphaltites suggest they were derived from a marine source rock deposited under anoxic or euxinic conditions, most likely a Cretaceous ocean anoxic event, and were generated within the early/main oil window. Here we identify a new type of semi-solid asphaltic bitumen collected following a severe storm event in 2016. Termed asphaltic tars, these viscous oils bear a strong geochemical resemblance to the asphaltites. Both oil types have high asphaltene contents, identical n -alkane carbon isotopic profiles and near identical source-specific sterane distributions. However, several notable geochemical variations can distinguish these new strandings from the asphaltites. The most notable of these differences include heavier bulk sulphur isotopic composition, extremely high abundances of Re and Os with distinct 187 Re/ 188 Os and 187 Os/ 188 Os values and thermal maturity parameters consistent with generation in the late oil window. The differences in sulphur isotopic composition and Re-Os systematics could be considered evidence that despite their other source-specific similarities, the asphaltic tars originated from a different source rock. However, alteration of these two parameters can occur due to thermochemical sulphate reduction. Conclusive identification of this alteration process typically relies on further diagnostic parameters which are unfortunately not available in the case of coastal oil strandings. This introduces uncertainty to the correlation of these two types of asphaltic oil. In either scenario, the similarities between these two types of oil suggest their source rock(s) contained highly comparable organic matter inputs. We therefore attribute the origin of these new asphaltic tar strandings to natural seepage from the offshore Bight Basin. Highlights: Report a new type of oil found on South Australian coastline termed asphaltic tar. Asphaltic tars share several source characteristics with well-studied asphaltites. Clear correlation to asphaltites is complicated by differences in thermal maturity. Asphaltic tars may have been altered by thermochemical sulphate reduction.